2020
DOI: 10.1016/j.apenergy.2019.114288
|View full text |Cite
|
Sign up to set email alerts
|

Building integrated solar concentrating systems: A review

Abstract: In the building sector, concerns towards the vast energy consumption has promoted the development of renewable energy technologies. In this regards, the solar concentration devices show a promising concept for building applications. However, the solar concentrators for application in buildings have many restrictions, which are different from the traditional solar concentrators. The main objective of this paper is to present a concise review on the building integrated concentrating devices, that have their own … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(29 citation statements)
references
References 98 publications
(145 reference statements)
0
29
0
Order By: Relevance
“…In Ref. [47], a review of the properties and functions of systems such as building-integrated concentrating photovoltaics (BICPV), building-integrated concentrating solar thermal (BICST), and building-integrated concentrating solar daylighting (BICSD), and BICPV/T, BICPV/D, BICST/D, and BICPV/T/D are presented. In Ref.…”
Section: Literature Overviewmentioning
confidence: 99%
“…In Ref. [47], a review of the properties and functions of systems such as building-integrated concentrating photovoltaics (BICPV), building-integrated concentrating solar thermal (BICST), and building-integrated concentrating solar daylighting (BICSD), and BICPV/T, BICPV/D, BICST/D, and BICPV/T/D are presented. In Ref.…”
Section: Literature Overviewmentioning
confidence: 99%
“…For crystalline Concentrator-based BIPV windows are also very attractive for less energy-hungry building integration. Low concentrating compound parabolic concentrator (CPC) [94] and luminescent solar concentrators (LSC) [95] are now dominating the major building-integrated concentrating photovoltaic research activity. Low concentrators are static which reduces the cost of the expensive solar tracker.…”
Section: Building Integrated and Applied Photovoltaic (Bipv/bapv) Tecmentioning
confidence: 99%
“…Recently, there are increasing interest of integrating the concentrating PV (CPV) technology into a building [11][12][13][14]. A report published in 2021 by the Market Data Forecast indicated that the global concentrating PV (CPV) is now exceeding $790 million and will continue to achieve a compound annual growth rate of 14.5% until 2026 [15].…”
Section: Introductionmentioning
confidence: 99%